Architectural lighting - Egan, M. David; Olgyay, Victor W. (Boston, Massachusetts : McGraw Hill Education, 2002)
The goal of this books is to graphically present the principles of vision and the behavior of light in the built environment.
1. Vision and perception -- 2. Properties of light -- 3. Natural light in buildings -- 4. Electric light -- 5. Light and form -- 6. Lightning calculation methods -- 7. Design tools -- 8. Design process -- References on lighting -- Appendices -- Indexes.
Keywords: LIGHTING, ARCHITECTURAL AND DECORATIVE